Visualized study of wetting enhancement and thermal performance of fiber-coated indirect evaporative cooler. (25th February 2023) - Chen, Yi; Yan, Huaxia; Min, Yunran
Highlights: Poor wetting can be identified for aluminum plates by visualized study. The tested fiber fabric shows superior wicking and diffusivity ability. Full wet is achieved for fiber-coated core under recommended spray parameters. Thermal conductivity of fiber-coated plate increases with water content. Effect of thermal resistance of fiber coating can be ignored under wet conditions. Abstract: Poor wetting is a serious problem facing the traditional aluminum and polymer indirect evaporative cooler, which largely deteriorates its cooling performance. Therefore, a fiber coating (70% rayon + 30% polyester textile) is proposed to be attached to the plate heat exchanger walls to improve the wetting condition by its good moisture diffusion. Firstly, the characteristics of the fiber are evaluated by a laser microscope, wicking height and diffusivity tests. Then, its application on an indirect evaporative cooler is investigated. On one hand, to quantitatively evaluate the wetting enhancement by the fiber, comparative visualized experiments are carried out between fiber-coated and non-coated cooler to investigate the water distribution, wetting ratio and water retention at three typical core positions under different spraying time (5 s–180 s), water flow rate (2 L/min–6 L/min) and nozzle height (50 mm to 250 mm). The visualized experiment innovatively combines fluorescence display and digital image processing methods. On the other hand, the thermal conductivity of the fiber-coated plate is tested and used as input for the heat and mass transfer model of indirect evaporative cooler to predict the outlet air temperature. The results show that the non-coated plate suffers from uneven water distribution and low wetting ratio, but the fiber coating can significantly improve the wetting conditions by providing 100% wetting ratio in only 30 s under 150 mm nozzle height and 5 L/min flow rate. The influence of thermal resistance of wetted fiber on outlet air temperature is negligible, but the dry fiber will increase the supply air temperature by 0.3 °C.